Ultraviolet B irradiation induces skin accumulation of plasmacytoid dendritic cells: A possible role for chemerin. (May 2014) - Yin, Qili; Xu, Xiaofei; Lin, Yuli; Lv, Jiaoyan; Zhao, Lina; He, Rui
Abstract Photosensitivity represents a common feature for most forms of lupus erythematosus (LE) including cutaneous LE. Skin inflammatory infiltrates in response to ultraviolet (UV) exposure are closely involved in the development of skin lesions of LE patients. Skin-infiltrating plasmacytoid dendritic cells (pDCs), considered as a hallmark of cutaneous LE, contribute to its pathogenesis via the production of type I interferons (IFNs). Chemerin, a recently identified chemoattractant for pDCs through its functional receptor chemR23, was found to be elevated in skin lesions of LE patients. The aim of this study was to investigate the effect of UVB irradiation on skin pDC recruitment and chemerin expression. We found that UVB irradiation induced a rapid but transient influx of pDCs as well as a persistent infiltration of neutrophils and macrophages in the mouse skin. The mRNA expression levels of IRF-7, IFN-α and chemR23 were increased in UVB-irradiated skin. Furthermore, UVB irradiation up-regulated skin chemerin production and pDC accumulation in parallel, both of which reached their peaks simultaneously (24 h post-irradiation). Dermal fibroblasts seemed to be the major source of chemerin as evidenced by significantly increased chemerin secretion by UVB-irradiated dermal fibroblasts. More importantly, LE-prone MRL/lpr mouse exhibited greatly increased skin pDC accumulation and chemerin production in response to UVB irradiation, indicating their contributions to increased susceptibility of photosensitivity in the MRL/lpr mouse. Thus, our findings demonstrated that elevated chemerin expression positively correlates with pDC accumulation in UVB-irradiated skin, suggesting a role of chemerin in mediating skin recruitment of pDCs in response to UVB exposure.